Endovascular intervention with a low-profile visualized intraluminal support stent for ruptured, very small, wide-necked, intracranial aneurysms - Jian Li; De-Cai Xu; Hou-Yin Liu (Journal of the Pakistan Medical Association, 2021)
Published in August 2021